The role of inflammation in myopic retinopathy - Yang, Tianxiang; Qi, Jinyan; Xu, Heping (Frontiers in Ophthalmology, 2025)
High myopia is a global health concern, often leading to degenerative retinal changes known as myopic retinopathy. Although mechanical stress, hypoperfusion, extracellular matrix remodeling, and growth factor dysregulation have been implicated in the pathogenesis of myopic retinopathy, emerging evidence highlights the critical role of chronic low-grade inflammation. Both innate and adaptive immune systems participate in myopic retinopathy through systemic and local inflammation. Systemically, immune dysregulation is marked by elevated levels of complement proteins C3, autoantibodies anti-LIM and senesce nt cell antigen-like-containing domain protein 1 (anti-LIMS1), and altered circulating immune cells (increased neutrophils and basophils). Locally, retinal homeostasis disruption triggers intraocular inflammation, evidenced by higher levels of interleukin-6 (IL−6), IL−8, tumor necrosis factor α (TNF−α), C-C motif chemokine ligand-2 (CCL2), C−X−C motif chemokine ligand 10 (CXCL10) and activating the complement system. The inflammatory response involves signaling pathways such as JAK-STAT and complement cascades. This review summarizes recent advances in understanding immunological mechanisms underlying myopic retinopathy, offering insights to guide future research.